Do Business Conditions Drive FDI Inflows? A Decomposition Analysis Using B-READY Indicators - Hardi, Irsan; Çoban, Mustafa Necati; Maulana, Ar Razy Ridha; Idroes, Ghalieb Mutig; Mardayanti, Ulfa (Indatu Journal of Management and Accounting, 2025)
Foreign direct investment (FDI) is essential for economic development and business sustainability, and understanding the business conditions that attract it remains a key policy concern. This study adopts a decomposition approach by examining the impact of various B-READY indicators on FDI inflows in separate models, using cross-sectional data from 45 countries. To ensure methodological rigor, it applies three Robust Least Squares (RLS) estimation techniques: M-type, S-type, and MM-type. The findings reveal that six out of ten B-READY indicators exert a positive and statistically significant influence on FDI inflows. The significant B-READY indicators, such as business insolvency, dispute resolution, international trade, labor, market competition, and taxation, highlight critical factors that businesses consider when entering or expanding in foreign markets. These insights offer valuable guidance and practical implications not only for policymakers seeking to strengthen national investment environments, but also for businesses evaluating market readiness and investment risks in foreign economies.